2021
DOI: 10.1002/fsn3.2434
|View full text |Cite
|
Sign up to set email alerts
|

Texture, color, and sensory changes occurring in chocolate bars with filling during storage

Abstract: Chocolate is a semi-solid suspension of fine solid particles of sugar, cocoa, and milk powder (depending on the type), making about 70% total, in a continuous fat phase, consisting mostly of cocoa butter (Afoakwa, 2014). Chocolate shelf-life is limited by the changes in the polymorphic state of cocoa butter or by rancidity development in solid chocolate. The resistance of chocolate to fat bloom is closely related to the crystallization of cocoa butter (Fernandes et al., 2013).At least six crystal forms (I-IV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…The smaller particle size (4.06 μm) of WSPI in comparison with that of SMP (24 μm) also substantiates our observation. A similar trend was observed in milk-filled chocolate bars stored for 26 weeks . The hardness of chocolate remained almost the same after 180 days of production except for WSPC-5 and control.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The smaller particle size (4.06 μm) of WSPI in comparison with that of SMP (24 μm) also substantiates our observation. A similar trend was observed in milk-filled chocolate bars stored for 26 weeks . The hardness of chocolate remained almost the same after 180 days of production except for WSPC-5 and control.…”
Section: Resultssupporting
confidence: 79%
“…A similar trend was observed in milk-filled chocolate bars stored for 26 weeks. 32 The hardness of chocolate remained almost the same after 180 days of production except for WSPC-5 and control.…”
Section: Rheological Properties Of Wspcmentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies have reported the importance of tempering, temperature control, and storage to chocolate hardness parameter. The increase in bar hardness has been evaluated during storage and positively accepted by the panelists through sensory evaluation [22]. In addition, the storage or maturation process improves the chocolate crystal formation to be more stable [23].…”
Section: Introductionmentioning
confidence: 99%
“…Досліджено вплив температури зберігання (6, 12, 20, 30 ºС) та періоду (2, 6, 10, 18, 26 тижнів) на текстуру, колір і сенсорні характеристики плиток шоколаду. Встановлено, що температури 6 і 12 ºС були найбільш придатними для зберігання виробів [4].…”
unclassified